Tamann temperature directed synthesis of core-shell catalysts

CN118541216BActive Publication Date: 2026-10-20THE HONG KONG POLYTECHNIC UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380013478.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-12-22
Filing Date
2023-11-21
Publication Date
2026-10-20
Estimated Expiration
2043-11-21

AI Technical Summary

Technical Problem

然而,这些方法是高度特定于材料的,因此很难扩展到其它体系

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118541216B_ABST
    Figure CN118541216B_ABST
Patent Text Reader

Abstract

A method of making a core-shell nanoparticle, the method comprising: contacting a mixture comprising a first metal oxide, a first encapsulating material comprising an alkali or alkaline earth metal, and a second encapsulating material comprising a second metal oxide with hydrogen at a temperature above the hydrogen reduction temperature of the first metal oxide and below the decomposition temperature of the first encapsulating material, resulting in reduction of the first metal oxide and formation of metal nanoparticles at least partially encapsulated by a double metal oxide comprising the alkali or alkaline earth metal and the second metal, thereby forming the core-shell nanoparticle, wherein the Tamman temperature of the first encapsulating material is below the hydrogen reduction temperature of the first metal oxide.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-references to related applications

[0002] This application claims priority to U.S. Provisional Patent Application No. 63 / 434,899, filed December 22, 2022, the entire contents of which are incorporated herein by reference. Technical Field

[0003] This disclosure generally relates to a method for preparing core@shell catalysts with improved stability. Background Technology

[0004] Transition metal nanoparticles (M T Core-and-shell nanoparticles (NPs) exhibit excellent activity for many important catalytic reactions, such as the conversion of methane (CH4) or ammonia (NH3), but their poor stability hinders their practical application. This is because highly active surface atoms are generally thermodynamically unstable, leading to severe NP sintering through secondary nucleation, recrystallization, ripening, particle migration, and agglomeration. To maintain the stability of NPs, various methods have been developed. Among these, the core-and-shell architecture provides an advantageous structure, preventing sintering during high-temperature catalytic reactions by isolating the active nanoparticle core with a shell. The most commonly used core-and-shell synthesis method involves physically confining NPs within porous materials (e.g., silica, alumina, zeolites, etc.). Despite the variety of choices and abundant sources of confinement materials, the inert support often obstructs the active sites, thus reducing catalytic performance.

[0005] Alternatively, strong metal-support interactions (SMSI) have been designed to generate core-shell structures for stabilizing and modifying active metal NPs. For example, regarding important industrial Cu / ZnO / Al2O3 methanol synthesis catalysts, it has been found that partially reduced zinc oxide can interact with metallic Cu NPs via the SMSI effect, thereby forming a protective layer to prevent Cu NP sintering. Various SMSI metal-support compositions have been explored and investigated due to their unique geometry and sintering-resistant interfacial interactions. It has been observed that at the metal-support interface, reducible metal oxide substrates (e.g., TiO2, V2O3, CeO2, and Ta2O5) can be thermally activated at high temperatures in a hydrogen (H2) atmosphere and migrate to the surface of the metal NP (typically platinum group metals such as Pt, Pd, etc.), thereby forming NPs completely encapsulated by oxides. This unique SMSI metal-support structure not only significantly improves the thermodynamic stability of NPs against sintering but also imparts tunable versatility to catalytic performance by adjusting the core-shell interface.

[0006] Unfortunately, the high temperatures required for the thermal activation step of SMSI limit the application of this strategy to low-melting-point NPs. For metals with inherently low melting temperatures, such as Fe, Co, Ni, Cu, and Au, NPs tend to be sintered before encapsulation. Therefore, to achieve M… T The successful encapsulation of NP, in M T Activating the supported metal oxide with sufficient mobility prior to NP sintering is crucial. Several successful cases have been reported, such as HCO3- on Rh NPs supported in TiO2 and Nb2O5. x Adsorbate-mediated SMSI encapsulation, CO2-enhanced redox-inert MgO encapsulation on Au NPs, and adsorbate-induced SMSI reconstruction of commercial Cu / ZnO / Al2O3 maximize activity and stability. However, these methods are highly material-specific and therefore difficult to extend to other systems. Thus, a general approach for core@shell synthesis remains needed to address or overcome at least some of the aforementioned drawbacks. Summary of the Invention

[0007] This article provides a method for implementing M T A general and effective method for thermally induced SMSI packaging using NP (NP-based) technology. This method involves utilizing empirical Taman temperatures (T0). Tam The phenomenon described by the low-temperature (T) phenomenon describes how atoms in solid materials become looser and more mobile and reactive at temperatures approximately half the melting point. This phenomenon utilizes the low-temperature (T) phenomenon. Tam The compound's advantage lies in its ability to be thermally activated and reacted at relatively low temperatures. Once in M T Low T forms on NP Tam The coating of the compound can be further functionalized through solid-state reactions, thereby forming a highly thermally stable protective layer for the catalyst support.

[0008] In a first aspect, this document provides a method for preparing core-shell nanoparticles, the method comprising: contacting a mixture comprising a first encapsulation material containing a first metal oxide, an alkali metal or an alkaline earth metal, and a second encapsulation material containing a second metal oxide with hydrogen gas at a temperature higher than the hydrogen reduction temperature of the first metal oxide and lower than the decomposition temperature of the first encapsulation material, causing the first metal oxide to be reduced and forming metal nanoparticles at least partially encapsulated by a bimetallic oxide comprising the alkali metal or the alkaline earth metal and the second metal oxide, thereby forming the core-shell nanoparticles, wherein the Taman temperature of the first encapsulation material is lower than the hydrogen reduction temperature of the first metal oxide.

[0009] In some embodiments, the method further includes providing screening data on the enthalpy changes of possible reaction products of the reaction of a candidate first metal oxide, a candidate first encapsulation material, a candidate second encapsulation material, and hydrogen; and selecting the first encapsulation material and the second encapsulation material based on the screening data and the decomposition temperature of the candidate first encapsulation material.

[0010] In some implementations, the screening data is generated using a computer.

[0011] In some embodiments, the method further includes selecting the first encapsulation material and the second encapsulation material based on the hydrogen reduction temperature of the first metal oxide, the decomposition temperature of the first encapsulation material, and the Taman temperature of the first encapsulation material.

[0012] In some embodiments, the first metal oxide comprises a metal selected from the group consisting of V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Mo, Se, Sn, Pt, Ru, Pd, W, Ir, Os, Rh, Nb, Ta, Pb, Bi, Au, Ag, Sc, and Y.

[0013] In some embodiments, the first metal oxide is selected from the group consisting of CoO3, Co3O4, CoO, CuO, Cu2O, NiO, Ni2O3, Ag2O, AgO, FeO, Fe2O3, Fe3O4, ZnO, PdO, PdO2, PtO, and PtO2.

[0014] In some embodiments, the first encapsulation material comprises an alkali metal or alkaline earth metal salt, wherein the alkali metal or alkaline earth metal salt comprises one or more anions selected from the group consisting of carbonate, sulfate, nitrate, chloride, phosphate and acetylacetonate.

[0015] In some embodiments, the first encapsulation material includes CaCO3, MgCO3, SrCO3, BaCO3, NaCl, KCl, RbCl, Na2CO3, K2CO3, or Rb2CO3.

[0016] In some embodiments, the second metal oxide includes Al2O3, TiO2, SiO2, Ga2O3, In2O3, ZrO2, or a mixture thereof.

[0017] In some embodiments, the first metal oxide is selected from the group consisting of CoO3, Co3O4, CuO, Cu2O, NiO, Ni2O3, Ag2O, AgO, FeO, Fe2O3, Fe3O4, ZnO, PdO, PdO2, PtO, and PtO2.

[0018] In some embodiments, the bimetallic oxide includes MgAl2O4, CaAl2O4, SrAl2O4, BaAl2O4, MgTiO3, CaTiO3, SrTiO3, BaTiO3, MgGa2O4, CaGa2O4, SrGa2O4, BaGa2O4, MgIn2O4, CaIn2O4, SrIn2O4, BaIn2O4, MgZrO3, CaZrO3, SrZrO3, or BaZrO3.

[0019] In some embodiments, each of the core-shell nanoparticles comprises a shell and a core, wherein the shell comprises MgAl2O4, CaAl2O4, SrAl2O4, BaAl2O4, MgTiO3, CaTiO3, SrTiO3, BaTiO3, MgGa2O4, CaGa2O4, SrGa2O4, BaGa2O4, MgIn2O4, CaIn2O4, SrIn2O4, BaIn2O4, MgZrO3, CaZrO3, SrZrO3, or BaZrO3, and the core comprises Co, Cu, Ni, Ag, Fe, Zn, Pd, or Pt.

[0020] In some embodiments, the core-shell nanoparticles are selected from the group consisting of Co@BaAl2O4, Cu@BaAl2O4, Ni@BaAl2O4, Co@BaTiO3, Fe@MgGa2O4, Co@MgGa2O4 and Ni@BaZrO3.

[0021] In some embodiments, the core-shell nanoparticles have an average diameter of 10-15 nm.

[0022] In some embodiments, the method further includes calcining the mixture prior to the step of contacting the mixture with hydrogen.

[0023] In some embodiments, calcination is performed below the decomposition temperature of the first encapsulation material.

[0024] In some embodiments, the method further includes contacting a first metal nitrate, an alkali metal or alkaline earth metal nitrate, a second metal nitrate, and an alkali metal carbonate to form a coprecipitate; and calcining the coprecipitate to form the mixture.

[0025] In some embodiments, the method further includes providing screening data on the enthalpy changes of possible reaction products of the reaction of a candidate first metal oxide, a candidate first encapsulation material, a candidate second encapsulation material, and hydrogen; selecting the first encapsulation material and the second encapsulation material based on the screening data and the decomposition temperature of the candidate first encapsulation material; and selecting the first encapsulation material and the second encapsulation material based on the hydrogen reduction temperature of the first metal oxide, the decomposition temperature of the first encapsulation material, and the Taman temperature of the first encapsulation material.

[0026] In some embodiments, the first metal oxide comprises a metal selected from the group consisting of V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Mo, Se, Sn, Pt, Ru, Pd, W, Ir, Os, Rh, Nb, Ta, Pb, Bi, Au, Ag, Sc, and Y.

[0027] In some embodiments, the method further includes contacting a first metal nitrate, an alkali metal or alkaline earth metal nitrate, a second metal nitrate, and an alkali metal carbonate to form a coprecipitate; and calcining the coprecipitate to form the mixture.

[0028] The core-shell nanoparticles prepared according to the method described in this paper exhibit high heat resistance, good hydrothermal stability and excellent catalytic performance in a wide range of catalytic reactions, such as catalytic ammonia decomposition, dry reforming of methane, steam reforming of methane, methanol reforming, CO2 hydrogenation and selective catalytic reduction.

[0029] In this paper, by means of the corresponding M T oxides (M) T O x In-situ reduction to synthesize M T NP, to avoid cumbersome multi-step processes and active M T Processing of NP materials. To establish an SMSI package, T... Tam This is considered an indicator for selecting a suitable encapsulation material, i.e., a support, for a target metal catalyst. More specifically, such as Figure 1 As shown in Figure a, the T of the encapsulation material Tam (represented as T) Tam (Carrier) should be lower than M T O x reduction temperature (T) red (represented as T) red (M T O x Therefore, in M T During NP formation in T red (M T O x Encapsulation can occur under these conditions to suppress M. TExcessive particle growth. Simultaneously, the decomposition temperature (T) of the encapsulation material... dec (represented as T) dec (Carrier) must be higher than T red (M T O x To avoid high mobility loss due to phase / structure changes, a support material that can meet the T... Tam (Carrier) <T red (M T O x ) <T dec If the carrier follows simple rules, it is expected to exhibit high mobility, thus enabling it to perform well in T... red (M T O x Implement M under ) T NP's SMSI package.

[0030] As a proof-of-concept demonstration, low T was chosen. Tam Alkaline earth metal carbonates (M AE CO3 (a common catalyst promoter) was used as a candidate support. Common non-noble metals M... T O x (M T =Fe, Co, Ni, Cu) and M AE CO3(M AE The phase transition temperatures of the Mg, Ca, Sr, Ba combination are plotted on [the graph]. Figure 1 b in. T dec (M AE CO3) and T red (M T O x The measurements were taken using H2 temperature-programmed decomposition and reduction experiments (see [reference]). Figure 10-11 and Figure 36 (details), and T Tam (M AE CO3) was retrieved from the literature. Figure 1 In b, T dec (M AE CO3) and T Tam (M AE The area sandwiched between CO3 (shaded area) indicates the appropriate temperature window (or encapsulating window), if the corresponding T red (M T O x If it falls within this range, then theoretically it is easy to apply M. T NP is used for SMSI packaging. Experimental synthesis of a combination of Co and BaCO3 has been used to demonstrate this concept. In an H2 atmosphere, via T... redThe temperature near (Co3O4) is then used for a next heat treatment to obtain a uniformly distributed Co NP encapsulated in BaCO3 (i.e., Co@BaCO3) (see [link]). Figure 1 c. Figure 12 and Figure 38 This result demonstrates the proposed M-axis guided by Taman temperature. T The feasibility of NP's convenient thermal packaging strategy. Attached Figure Description

[0031] The foregoing aspects and many incidental advantages of the invention will be more readily understood by referring to the following detailed description in conjunction with the accompanying drawings.

[0032] Figure 1 The theoretical synthesis principle of thermally induced encapsulation based on Taman temperature. a) Schematic diagram of the design and synthesis principle of this thermally induced encapsulation strategy guided by Taman temperature. b) M... AE CO3 affects in-situ formation of M T A schematic diagram of the estimated suitable temperature range (or packageable window, shaded) for NP packaging. c. TEM, STEM images and elemental distribution maps of Co@BaCO3.

[0033] Figure 2 One-step heat treatment for metal encapsulation and capping functionalization. a) Schematic diagram of the subsequent capping functionalization step after thermally induced SMSI encapsulation. b) Rapid calculation and screening of the enthalpy change (ΔH) of possible products formed by the solid-state reaction between BaCO3, Al2O3, and Co3O4 in H2. ΔH was obtained from the Materials Project database. The lower the ΔH, the more stable the reaction products. c) STEM image and elemental distribution map of Co@BaAl2O4. d) EXAFS fitting curves of the Co K-edge (top) and Ba L3-edge (bottom) of Co@BaAl2O4 in R space. e) SXRD pattern of Co@BaAl2O4. Rietveld's retouching.

[0034] Figure 3 Real-time observation and mechanism study of encapsulation. (a) In-situ STEM image of the initial state at room temperature, above T. Tam (BaCO3) diffusion stage (b) (dashed lines represent the expansion of the BaCO3 boundary, and dashed circles represent vacancies inside BaCO3), at temperatures higher than T redThe Co NP formation stage (c) during (Co3O4) (circles indicate Co nucleation and growth), and the Co@BaAl2O4 formation stage after the solid-state reaction between BaCO3 and Al2O3 (d). e, Schematic diagram of the mechanism of this thermally induced encapsulation strategy guided by Taman temperature. f, XRD patterns of 40Co:20Ba:40Al reduced at different temperatures from room temperature to 700°C. g, In-situ Raman spectra of 40Co:20Ba:40Al reduced at different temperatures from room temperature to 700°C (left), and MS signal of the outlet gas monitored during H2 reduction (right) (m / z = 2 for H2, m / z = 18 for H2O, and m / z = 28 for CO).

[0035] Figure 4 Encapsulated nanocatalysts can achieve excellent catalytic performance. a) Comparison of H2 productivity at 500 °C between Co@BaAl2O4 and selected core@shell catalysts for the NH3 decomposition reaction (see details). Figure 46 b), H2 productivity during NH3 decomposition reaction relative to core@shell Co@BaAl2O4, unencapsulated catalyst containing Co / Al2O3, and Co / BaAl2O4 sample prepared by co-precipitation and polyol methods, based on continuous run time. At 30,000 mL g cat -1 h -1 Performance was evaluated at gravity space velocity (WHSV). c, Histograms of CoNP size distribution in unencapsulated Co / BaAl2O4-coprecipitates before and after 80 hours of NH3 decomposition reaction; insets show TEM images of the corresponding samples. d, Histograms of Co NP size distribution in core@shell Co@BaAl2O4 before and after 80 hours of NH3 decomposition reaction; insets show TEM images of the corresponding samples. e, STEM images (top) and elemental distribution maps (bottom) of Cu@MgAl2O4, Ni@BaAl2O4, and Co@BaTiO3.

[0036] Figure 5 The precursor was prepared via coprecipitation synthesis and heat treatment. mM T :nM AE Schematic diagram of the synthesis process of :2nAl precursor and subsequent heat treatment process.

[0037] Figure 6 XRD measurement of gas-sensitive samples. A gas-tight XRD holder for gas-sensitive samples.

[0038] Figure 7In-situ Raman apparatus. (a) In-situ Raman gas cell, with the gas flow direction marked. (bc) Experimental setup of the in-situ example, showing the gas cell mounted on the Raman imaging microscope platform. (d) Temperature and flow control unit of the in-situ Raman apparatus.

[0039] Figure 8 In-situ STEM setup. (a) Schematic diagram showing the components of the Protochips Atmosphere gas holder. (b) Electronic chips used in the Protochips Atmosphere gas holder. (c) Atmosphere system used for in-situ STEM experiments.

[0040] Figure 9 Schematic diagram of the NH3 decomposition performance testing device.

[0041] Figure 10 M AE CO3 decomposition temperature (T) dec The determination of MS signals during the H2 temperature-programmed decomposition of (a) MgCO3, (b) CaCO3, (c) SrCO3, and (d) BaCO3. The temperature was maintained at 800 °C for 3 hours (950 °C for BaCO3) after reaching 800 °C. The unshaded area (x = 50 to 800 °C) shows the MS signal as a function of temperature. The blue shaded area (x = 0 to 180 min) shows the MS signal as a function of retention time at 800 °C (950 °C for BaCO3). The maximum value of each decomposition curve was determined as the corresponding T0. dec (M AE CO3).

[0042] Figure 11 M T O x reduction temperature (T) red The MS signals during the H2 temperature-programmed reduction of (a) Fe2O3, (b) Co3O4, (c) NiO, and (d) CuO were measured. The temperature was maintained at 800°C for 3 hours (950°C for Fe2O3) after reaching 800°C. The unshaded area (x = 50 to 800°C) shows the MS signal variation with temperature. The blue shaded area (x = 0 to 180 min) shows the MS signal variation with retention time at 800°C (950°C for Fe2O3). The orange shaded area represents the reported H2 temperature-programmed reduction temperature range, indicating that our measurements are within a reasonable range based on previous reports (detailed reported data can be found in...). Figure 37 The maximum value of each reduction curve is determined as the corresponding T. red (M T O x ).

[0043] Figure 12 A proof-of-concept demonstration was conducted by constructing a Co@BaCO3 package. Structural and fabrication identification of C(500)-R(500)-67Co:33Ba: (a) XRD pattern and (b) Co NP size distribution measured by low-magnification TEM images.

[0044] Figure 13 High-throughput screening of possible products of solid-state reaction. All possible products of the solid-state reaction between BaCO3+Al2O3+Co3O4+H2 (top figure) and the top 20 possible products (bottom figure) along with their corresponding enthalpy changes (ΔH).

[0045] Figure 14 Construction of the Co@BaAl2O4 encapsulation structure. (a) Top: XRD pattern of C(500)-40Co:20Ba:40Al. Bottom: XRD pattern of C(500)-R(700)-40Co:20Ba:40Al. It can be observed that during H2 heat treatment, Co3O4 is reduced to Co NP and BaAl2O4 is formed through a solid-state reaction between BaCO3 and Al2O3. (b) Size distribution of Co NP measured by low-magnification TEM image of C(500)-R(700)-40Co:20Ba:40Al.

[0046] Figure 15 Morphological and structural studies of Co@BaAl2O4 from TEM. (a) High-resolution TEM image of Co@BaAl2O4. The dashed box indicates the region where Fast Fourier Transform (FFT) was performed. (b) FFT pattern calculated from the dashed box, showing the fcc Co phase diffraction pattern along the

[011] region axis. (c) FFT pattern calculated from the dashed box, showing the fcc Co phase diffraction pattern along the

[011] region axis. The diffraction pattern of the BaAl2O4 phase along the region axis.

[0047] Figure 16 Electronic properties and local structure of Co in Co@BaAl2O4. (a) Co K-edge XANES spectra of 40Co:20Ba:40Al, C(500)-40Co:20Ba:40Al and C(500)-R(700)-40Co:20Ba:40Al, and Co foil for comparative purposes. (b) K-edge XANES spectra of 40Co:20Ba:40Al, C(500)-40Co:20Ba:40Al and C(500)-R(700)-40Co:20Ba:40Al. 3Weighted Co K-side Fourier Transform (FT) EXAFS. (c) Co K-side EXAFS fitting curve of C(500)-40Co:20Ba:40Al. (d) Co K-side EXAFS fitting curve of C(500)-R(700)-40Co:20Ba:40Al. (eh)(e) WT representation of Co K-side EXAFS signals of C(500)-40Co:20Ba:40Al, (f) C(500)-R(700)-40Co:20Ba:40Al, (g) theoretical Co3O4 model and (h) standard Co foil.

[0048] Figure 17 Electronic properties and local structure of Ba in Co@BaAl2O4. (a) L3-edge XANES spectra of Ba in 40Co:20Ba:40Al, C(500)-40Co:20Ba:40Al and C(500)-R(700)-40Co:20Ba:40Al. (b) k-side XANES spectra of Ba in 40Co:20Ba:40Al, C(500)-40Co:20Ba:40Al and C(500)-R(700)-40Co:20Ba:40Al. 3 Weighted Ba L3-side Fourier Transform (FT) EXAFS. (c) Ba L3-side EXAFS fitting curve for 40Co:20Ba:40Al. (d) Ba L3-side EXAFS fitting curve for C(500)-40Co:20Ba:40Al. (e) Ba L3-side EXAFS fitting curve for C(500)-R(700)-40Co:20Ba:40Al. (fj)(f) 40Co:20Ba:40Al, (g) C(500)-40Co:20Ba:40Al, (h) C(500)-R(700)-40Co:20Ba:40Al, (i) WT representation of Ba L3-side EXAFS signals for theoretical BaCO3 model and (j) theoretical BaAl2O4 model.

[0049] Figure 18 Oxygen vacancies in the BaAl2O4 capping layer of Co@BaAl2O4. (a) XPS spectrum of the O1s core level of Co@BaAl2O4, showing a peak at a binding energy of 532.2 eV attributed to oxygen vacancies in the BaAl2O4 lattice. (b) EPR spectrum of BaAl2O4, showing a signal with a splitting factor value (g) of 1.9806, corresponding to an oxygen vacancy (V) with a single trapped electron. O +(c) Ar adsorption-desorption isotherms of Co@BaAl2O4 and pristine BaAl2O4. (d) Density functional theory (DFT) pore size distribution curves of Co@BaAl2O4 and pristine BaAl2O4.

[0050] Figure 19 Low T Tam M AE The necessity of CO3 as a promoter. (ad) Structural and structural identification of Co / BaAl2O4-coprecipitate: (a) XRD pattern of Co / BaAl2O4-coprecipitate, (bc) TEM image of Co / BaAl2O4-coprecipitate, and (d) Co NP size distribution of Co / BaAl2O4-coprecipitate measured by low-magnification TEM image. (eh) Structural and structural identification of Co / BaAl2O4-polyol: (e) XRD pattern of Co / BaAl2O4-polyol, (fg) TEM image of Co / BaAl2O4-polyol, and (h) Co NP size distribution of Co / BaAl2O4-polyol measured by low-magnification TEM image.

[0051] Figure 20 Elemental composition analysis during the synthesis process. (a) SEM image of 40Co:20Ba:40Al, (b) SEM image of C(500)-40Co:20Ba:40Al, and (c) SEM image of C(500)-R(700)-40Co:20Ba:40Al. (d) EDX chemical composition analysis of 40Co:20Ba:40Al; (e) EDX chemical composition analysis of C(500)-40Co:20Ba:40Al; and (f) EDX chemical composition analysis of C(500)-R(700)-40Co:20Ba:40Al. It can be observed that the atomic ratio of Co, Ba, and Al remains unchanged at approximately 2:1:2 throughout each step of the synthesis process, with no significant loss, which is consistent with the original precursor metal composition.

[0052] Figure 21 Morphological evolution during the synthesis process. TEM images of the sample at different stages of the synthesis process (i.e., precipitation, calcination, and heat treatment in H2).

[0053] Figure 22Morphology of the mixed metal precursors before H2 heat treatment. (a) Low-magnification TEM image of the precursor C(500)-40Co:20Ba:40Al. (b) TEM image of the BaCO3 region. The inset is the corresponding FFT pattern for the entire region, corresponding to the (230), (111), (220), and (011) planes of the BaCO3 phase. (cd) High-resolution TEM image of the Co / Al oxide region. The inset of (d) is the FFT pattern calculated from the marked Al2O3 rods, showing the morphology along the... The diffraction pattern of the Al2O3 phase along the axis.

[0054] Figure 23 Real-time observation of elemental distribution evolution via in-situ STEM-EDX. (a) Calcinated precursor C(500)-40Co:20Ba:40Al, (b) Sample after in-situ reduction at 500℃ for 30 minutes, and (c) EDX pattern of the same region of the sample after in-situ reduction at 800℃ for 30 minutes. (d) EELS pattern and corresponding selected area electron diffraction (SAED) pattern of the sample after in-situ reduction at 800℃ for 30 minutes.

[0055] Figure 24 Evaluation of the effect of the electron beam on the observed samples. (a) EDX spectrum of the mixed metal precursor outside the in-situ tracking region. (b) EELS spectrum of the sample outside the in-situ tracking region after reduction at 800 °C for 30 minutes.

[0056] Figure 25 Reliability of the NH3 decomposition performance testing equipment and accuracy of product composition analysis. (a) Comparison of NH3 conversion rates between reported benchmark catalysts and our validation experimental results. (b) NH3 conversion rates obtained by MS and titration analysis.

[0057] Figure 26 Catalytic performance of Co@BaAl2O4 catalyst for NH3 decomposition. The NH3 decomposition conversion and H2 production rate relative to the Co@BaAl2O4 catalyst change with reaction temperature. At 30,000 mL g cat -1 h -1 Performance was evaluated at heavy time airspeed (WHSV) and 1 atm.

[0058] Figure 27 Co@BaAl2O4 represents one of the most efficient catalysts on record, both in non-noble metal and noble metal catalysts. A comparison of NH3 conversion between Co@BaAl2O4 (red spheres) and reported Ru-based and non-noble metal-based catalysts is shown. The size of the spheres represents the WHSV value. Larger sphere diameters correspond to higher WHSVs. Detailed data can be found at [link to relevant documentation]. Figure 47 .

[0059] Figure 28 S24. Sintering of unencapsulated structures under harsh thermal conditions: Co / BaAl2O4-coprecipitated samples. Co / BaAl2O4-coprecipitated samples before (blue) and after (green) 80-hour NH3 decomposition reaction (see synthesis details). Figure 21 Structural and structural identification of Co NPs: (a) XRD patterns before and after the reaction. (bc) TEM image before the reaction. (d) Co NP size distribution before the reaction, measured by low-magnification TEM. (ef) TEM image after the reaction. (g) Co NP size distribution after the reaction, measured by low-magnification TEM image.

[0060] Figure 29 Sintering of unencapsulated structures under harsh thermal conditions: Co / Al2O3 samples. Structural and structural identification of Co / Al2O3 before and after 80-hour NH3 decomposition reaction: (a) XRD patterns before and after the reaction. (bc) TEM image before the reaction. (d) Co NP size distribution before the reaction as measured by low-magnification TEM. (ef) TEM image after the reaction. (g) Co NP size distribution after the reaction as measured by low-magnification TEM image. Co / Al2O3 was synthesized by the following steps: (i) Co(NO3)2 and Al(NO3)3 co-precipitated in a 2:3 molar ratio, i.e., 40Co:60Al; (ii) calcined in air at 500 °C, i.e., C(500)-40Co:60Al; (iii) heat-treated with H2 at 500 °C, i.e., C(500)-R(500)-40Co:60Al.

[0061] Figure 30 Structural stability of Co@BaAl2O4 with encapsulated structure under harsh thermal conditions. (a) XRD patterns of the Co@BaAl2O4 catalyst before (blue) and after 80 hours of NH3 decomposition reaction; (b) Co 3p XPS spectra of the Co@BaAl2O4 catalyst before and after 80 hours of NH3 decomposition reaction, with blank circles representing experimental XPS data and solid lines representing Gaussian and Lorentz convolutions; (c) Ba 4d XPS spectra of the Co@BaAl2O4 catalyst before and after 80 hours of NH3 decomposition reaction, with blank circles representing experimental XPS data and solid lines representing Gaussian and Lorentz convolutions; (d) k of Co@BaAl2O4 after the reaction. 3 Weighted Fourier Transform (FT) Co K-edge (top figure) and Ba L3-edge (bottom figure) EXAFS and corresponding EXAFS fitting: circles represent experimental data, and solid lines represent EXAFS fitting results.

[0062] Figure 31Excellent environmental tolerance and reusability in practical applications. NH3 conversion rate during a five-month test period (including temperature fluctuations, system on / off cycles, and catalyst unloading / reloading).

[0063] Figure 32 The encapsulated Co@BaAl2O4 exhibits good stability in the CH4 dry reforming reaction. CH4 conversion, CO2 conversion, H2 selectivity, and H2 / CO ratio are compared with those of the Co@BaAl2O4 catalyst at different continuous run times during the CH4 dry reforming reaction. (31,765 mL g) cat -1 h -1 Performance was evaluated at WHSV and 750°C. The molar ratio of CH4:CO2:Ar in the inlet gas was 0.45:0.45:0.10. The dashed line represents the thermodynamic equilibrium of CH4 and CO2 conversion.

[0064] Figure 33 Ni@BaAl2O4 core@shell synthesis. (a) All (top) and top 20 (bottom) possible products of the solid-state reaction between BaCO3 + Al2O3 + NiO + H2 and the corresponding ΔH. (b) XRD patterns of C(500)-40Ni:20Ba:40Al and Ni@BaAl2O4. (c) Size distribution of Ni NPs measured by low-magnification TEM images of Ni@BaAl2O4.

[0065] Figure 34 Core-shell synthesis of Cu@MgAl2O4. (a) All (top) and top 20 (bottom) possible products of the solid-state reaction between MgCO3 + Al2O3 + CuO + H2 and the corresponding enthalpy changes (ΔH). (b) XRD patterns of C(300)-40Cu:20Mg:40Al and Cu@MgAl2O4. (c) Size distribution of Cu NPs measured from low-magnification TEM images of Cu@MgAl2O4.

[0066] Figure 35 Co@BaTiO3 core@shell synthesis. (a) All (top) and top 20 (bottom) possible products of the solid-state reaction between BaCO3+TiO2+CoO+H2 and the corresponding enthalpy change (ΔH). (b) XRD patterns of C(500)-50Co:25Ba:25Ti and Co@BaTiO3. (c) Size distribution of Co NPs as measured by low-magnification TEM images of Co@BaTiO3.

[0067] Figure 36 M retrieved from the literature AE CO3(M AE=Mg, Ca, Sr, Ba) and M T (M T Melting point (T) of Fe, Co, Ni, Cu melt ) and Taman temperature (T Tam M AE The experimental decomposition temperature of CO3 (T) dec ) and M T O x reduction temperature (T) red ). * The crystal lattice of a solid compound maintains a constant vibrational motion at normal room temperature. As the temperature increases, the amplitude of ion movement increases until they reach their melting point and transform into a liquid phase. The Taman temperature (T0) is the temperature at which ions move. Tam T is an absolute temperature at which the atoms in the crystal lattice of a solid bulk material become "loose," thus becoming more reactive or more easily diffused by other molecules. It has been reported that T... Tam The absolute melting point of the compound (T) melt Half of ).

[0068] Figure 37 M from the H2 temperature-programmed reduction spectra retrieved from the literature T O x To M T The reduction temperature of NP.

[0069] Figure 38 Estimation of Co NP crystallite size in C(500)-R(500)-67Co:33Ba. The 67Co:33Ba precursor was synthesized by co-precipitation of Co(NO3)2 and Ba(NO3)2 solution in BaCO3 solution, followed by calcination in air at 500 °C and heat treatment in H2 at 500 °C. The final product was designated C(500)-R(500)-67Co:33Ba. Figure 12 a shows the XRD pattern of C(500)-R(500)-67Co:33Ba, in which BaCO3 and fcc Co are observed, indicating that Co3O4 has been reduced to fcc Co while BaCO3 remains undecomposed.

[0070] Figure 39 Estimation of Co NP crystallite size.

[0071] Figure 40 Co K-edge EXAFS fitting parameters for C(500)-40Co:20Ba:40Al and C(500)-R(700)-40Co:20Ba:40Al. *Co K-edge EXAFS fitting results, where CN is the average coordination number, R is the distance from the absorber atom, and σ 2The Debye-Waller factor is used. The R-factor represents the quality factor of the fit, and ΔE0 represents the energy shift of the absorbed edge energy E0.

[0072] Figure 41 The coordination environment for Co atoms in theoretical Co3O4 and Co metal models.

[0073] Figure 42 Ba L3 edge EXAFS fitting parameters for 40Co:20Ba:40Al, C(500)-40Co:20Ba:40Al and C(500)-R(700)-40Co:20Ba:40Al.

[0074] Figure 43 The coordination environment for Ba atoms absorbed in the theoretical BaCO3 and BaAl2O4 models.

[0075] Figure 44 Estimation of Co NP crystallite size in Co / BaAl2O4-coprecipitate and Co / BaAl2O4-polyol.

[0076] Figure 45 The atomic ratios of Co, Ba, and Al in 40Co:20Ba:40Al, C(500)-40Co:20Ba:40Al, and C(500)-R(700)-40Co:20Ba:40Al were measured by SEM-EDX.

[0077] Figure 46 Catalytic performance of Co@BaAl2O4 and other reported core@shell catalysts for the decomposition of NH3 at 1 atmosphere.

[0078] Figure 47 The study selected from the literature used high WHSV (>15,000 mL g) at 1 atmosphere. cat -1 h -1 Catalysts with high NH3 decomposition performance (NH3 conversion rate ≥95%).

[0079] Figure 48 Estimation of Co NP crystallite size in Co / BaAl2O4- coprecipitate before and after 80 hours of NH3 decomposition reaction.

[0080] Figure 49 Estimation of Co NP crystallite size in Co / Al2O3 before and after 80 hours of NH3 decomposition reaction.

[0081] Figure 50 Estimation of Co NP crystallite size in Co@BaAl2O4 before and after 80 hours of NH3 decomposition reaction.

[0082] Figure 51 Co K-edge EXAFS fitting parameters of Co@BaAl2O4 after reaction.

[0083] Figure 52 EXAFS fitting parameters of Ba L3 edge of Co@BaAl2O4 after reaction.

[0084] Figure 53 The catalysts for CH4 dry reforming and their catalytic performance under the corresponding conditions are reported.

[0085] Figure 54 M T Estimation of NP crystallite size. Detailed Implementation

[0086] definition

[0087] Throughout this disclosure, unless the context otherwise requires, the word “comprise” or variations thereof such as “comprises” or “comprising” should be understood to imply inclusion of the stated integers or groups of integers, but not to exclude any other integers or groups of integers. It should also be noted that in this disclosure, and particularly in the claims and / or paragraphs, terms such as “comprises,” “comprised,” “comprising,” etc., may have the meanings given to them by U.S. patent law, for example, they may mean “includes,” “included,” “including,” etc.; and terms such as “consisting essentially of” and “consists essentially of” have the meanings given to them by U.S. patent law, for example, they cover elements not expressly stated, but exclude elements present in the prior art or affecting the essential or novel features of the invention.

[0088] Furthermore, throughout this disclosure and claims, unless the context otherwise requires, the word “include” or variations such as “includes” or “including” should be understood to imply inclusion of the stated integers or groups of integers, but not to exclude any other integers or groups of integers.

[0089] Unless otherwise specified, the singular as used herein includes the plural (and vice versa). Furthermore, where the term “about” precedes a quantitative value, this teaching also includes the specific quantitative value itself, unless otherwise specified. As used herein, unless otherwise stated or inferred, the term “about” means a difference from the nominal value of ±10%, ±7%, ±5%, ±3%, ±1%, or ±0%.

[0090] This disclosure provides a method for preparing core-shell nanoparticles, the method comprising: contacting a mixture comprising a first encapsulation material containing a first metal oxide, an alkali metal or an alkaline earth metal, and a second encapsulation material containing a second metal oxide with hydrogen gas at a temperature higher than the hydrogen reduction temperature of the first metal oxide and lower than the decomposition temperature of the first encapsulation material, causing the first metal oxide to be reduced and forming metal nanoparticles at least partially encapsulated by a bimetallic oxide containing an alkali metal or an alkaline earth metal and a second metal oxide, thereby forming core-shell nanoparticles, wherein the Taman temperature of the first encapsulation material is lower than the hydrogen reduction temperature of the first metal oxide.

[0091] The first metal oxide may comprise a metal selected from the group consisting of V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Mo, Se, Sn, Pt, Ru, Pd, W, Ir, Os, Rh, Nb, Ta, Pb, Bi, Au, Ag, Sc, and Y. The oxidation state of the metal may be 1+, 2+, 3+, 4+, 5+, or 6+. In some embodiments, the metal oxide comprises V. 2+ V 3+ V 4+ V 5+ Cr 2+ Cr 3+ Cr 6+ Fe 2+ Fe 3+ Co 2+ Co 3+ Ni 2+ Ni 3+ Cu 1+ Cu 2+ Zn 1+ Mo 2+ Mo 3+ Mo 4+ Mo 5+ Mo 6+ Se 2+ Se 4+ Sn 2+ Sn 4+ Pt 2+ Pt 4 + Ru 2+ Ru3+ Ru 4+ Ru 5+ Ru 6+ Pd 2+ Pd 4+ W 2+ W 3+ W 4+ W 5+ W 6+ Ir 1+ Ir 3+ Os 3+ Os 4+ Os 5+ Os 6+ ,Rh 1 + ,Rh 3+ 、Nb 3+ 、Nb 4+ 、Nb 5+ Ta 3+ Ta 4+ Ta 5+ Pb 2+ Pb 4+ Bi 1+ Bi 2+ Au 1+ Au 3+ Ag 1+ ,Sc 3+ Or Y 3+ Exemplary metal oxides include, but are not limited to, CoO3, Co3O4, CoO, CuO, Cu2O, NiO, Ni2O3, Ag2O, AgO, FeO, Fe2O3, Fe3O4, ZnO, PdO, PdO2, PtO, and PtO2.

[0092] Alkali metals can be lithium, sodium, potassium, rubidium, or cesium. Alkali earth metals can be beryllium, magnesium, calcium, strontium, or barium. In some embodiments, the first encapsulating material may include an alkali metal salt or an alkaline earth metal salt. In some embodiments, the alkali metal salt or alkaline earth metal salt comprises one or more anions selected from the group consisting of carbonate, sulfate, nitrate, and chloride ions. Exemplary alkali metal salts or alkaline earth metal salts include, but are not limited to, NaCl, KCl, RbCl, Na₂CO₃, K₂CO₃, Rb₂CO₃, CaCO₃, MgCO₃, SrCO₃, and BaCO₃.

[0093] The first encapsulating material can be any alkali metal salt or alkaline earth metal salt with a Taman temperature lower than the hydrogen reduction temperature of the first metal oxide and a decomposition temperature higher than the hydrogen reduction temperature of the first metal oxide. The Taman temperature of the first encapsulating material can be readily determined based on its melting point. The decomposition temperature of the first encapsulating material can be determined experimentally by confirming the temperature at which it begins to decompose under reaction conditions involving the mixture and hydrogen.

[0094] The second encapsulant may contain a second metal oxide selected from the group consisting of Al2O3, TiO2, SiO2, Ga2O3, In2O3, ZrO2 and mixtures thereof.

[0095] Under the reaction conditions, the first encapsulating material and the second encapsulating material can undergo a solid-state reaction at a temperature higher than the Taman temperature of the first encapsulating material, thereby forming a bimetallic oxide that at least partially encapsulates metal nanoparticles. The bimetallic oxide comprises an alkali metal or alkaline earth metal and a second metal oxide. In some embodiments, the bimetallic oxide partially surrounds multiple metal nanoparticles, for example, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, or more metal nanoparticles. The composition of the bimetallic oxide shell will vary based on the selection of the first encapsulating material and the second encapsulating material. In some embodiments, the bimetallic oxide is MgAl2O4, CaAl2O4, SrAl2O4, BaAl2O4, MgTiO3, CaTiO3, SrTiO3, BaTiO3, MgGa2O4, CaGa2O4, SrGa2O4, BaGa2O4, MgIn2O4, CaIn2O4, SrIn2O4, BaIn2O4, MgZrO3, CaZrO3, SrZrO3, or BaZrO3.

[0096] In some embodiments, the metal nanoparticles contain V 0 Cr 0 Mn 0 Fe 0 Co 0 Ni 0 Cu 0 Zn 0 Mo 0 Se 0 Sn 0 Pt 0 Ru 0 Pd 0 W 0 Ir 0 Os 0 ,Rh 0 、Nb 0Ta 0 Pb 0 Bi 0 Au 0 Ag 0 ,Sc 0 Or Y 0 .

[0097] The hydrogen reduction temperature of the first metal oxide is the temperature required to reduce at least a portion of the first metal oxide to form zero-valent metal nanoparticles under reaction conditions involving contact between the mixture and hydrogen. The hydrogen reduction temperature of the first metal oxide can be determined experimentally by those skilled in the art using well-known experimental techniques. In some embodiments, the reduction of the first metal oxide produces a mixture of reduction products, which includes partially reduced metallic substances. The core may contain at least 5% wt / wt, at least 10% wt / wt, at least 20% wt / wt, at least 30% wt / wt, at least 40% wt / wt, at least 50% wt / wt, at least 60% wt / wt, at least 70% wt / wt, at least 80% wt / wt, at least 90% wt / wt, at least 95% wt / wt, at least 97% wt / wt, at least 98% wt / wt, at least 99% wt / wt, or at least 99.9% wt / wt of zero-valent metal relative to the total weight of the zero-valent metal, the partially reduced products of the first metal oxide, and the unreacted first metal oxide. In some embodiments, the core contains 5-99.9% wt / wt, 10-99.9% wt / wt, 20-99.9% wt / wt, 30-99.9% wt / wt, 40-99.9% wt / wt, 50-99.9% wt / wt, 60-99.9% wt / wt, 70-99.9% wt / wt, 80-99.9% wt / wt, 90-99.9% wt / wt, 95-99.9% wt / wt, 30-99% wt / wt, 30-90% wt / wt, 30-80% wt / wt, 30-70% wt / wt, 30-60% wt / wt, 40-60% wt / wt, or 40-50% wt / wt of zero-valent metal relative to the total weight of the zero-valent metal, the partially reduced product of the first metal oxide, and the unreacted first metal oxide.

[0098] Core-shell nanoparticles prepared according to the method described herein may comprise one or more cores and a shell at least partially surrounding the one or more cores. In some embodiments, the core-shell nanoparticles comprise one or more cores and a shell, said core comprising V 0 Cr 0 Mn 0 Fe 0 Co 0 Ni 0 Cu0 Zn 0 Mo 0 Se 0 Sn 0 Pt 0 Ru 0 Pd 0 W 0 Ir 0 Os 0 ,Rh 0 、Nb 0 Ta 0 Pb 0 Bi 0 Au 0 Ag 0 ,Sc 0 Or Y 0 The shell comprises MgAl2O4, CaAl2O4, SrAl2O4, BaAl2O4, MgTiO3, CaTiO3, SrTiO3, BaTiO3, MgGa2O4, CaGa2O4, SrGa2O4, BaGa2O4, MgIn2O4, CaIn2O4, SrIn2O4, BaIn2O4, MgZrO3, CaZrO3, SrZrO3, or BaZrO3. Exemplary core-shell nanoparticles include, but are not limited to, Co@BaAl2O4, Cu@BaAl2O4, Ni@BaAl2O4, Co@BaTiO3, Fe@MgGa2O4, Co@MgGa2O4, and Ni@BaZrO3.

[0099] In some embodiments, the selection of the first encapsulating material is based on the hydrogen reduction temperature of the first metal oxide, the decomposition temperature of the first encapsulating material, and the Taman temperature of the first encapsulating material. More specifically, for a given first metal oxide, a suitable first encapsulating material may have a Taman temperature below the hydrogen reduction temperature of the given first metal oxide and a decomposition temperature above the given first metal oxide. In some embodiments, the selection of a suitable first encapsulating material for a given first metal oxide is determined by screening a list of candidate first encapsulating materials with respect to the hydrogen reduction temperature of the given first metal oxide, including the Taman temperatures and decomposition temperatures of the candidate first encapsulating materials, thereby identifying suitable first encapsulating materials from this list that have a Taman temperature below the hydrogen reduction temperature of the given first metal oxide and a decomposition temperature above the given first metal oxide. Screening can be performed manually, for example by referring to a table or list, or it can be performed using a computer.

[0100] The Taman temperature of the first encapsulation material, the decomposition temperature of the first encapsulation material, and the hydrogen reduction temperature of the first metal oxide can be determined experimentally and / or by reference.

[0101] The selection of the first and second encapsulation materials can be based on data collected by screening the enthalpy changes of potential reaction products of the candidate first metal oxide, candidate first encapsulation material, candidate second encapsulation material, and hydrogen according to the decomposition temperature of the candidate first encapsulation material. An enthalpy-favorable reaction to produce the bimetallic oxide can be selected at a reaction temperature lower than the decomposition temperature of the candidate first encapsulation material, which determines the selection of the first and second encapsulation materials. This process is in... Figure 13 The diagram shows the possible reaction products of the solid-state reaction BaCO3 + Al2O3 + Co3O4 + H2, arranged from most stable to least stable based on the enthalpy change (ΔH) of the possible products. Among the most stable possible products, BaAl2O4 is selected because the reaction temperature required for its preparation is lower than the decomposition temperature of BaCO3. In some embodiments, the step of screening the enthalpy changes of potential reaction products is performed using the Materials Project database in a computer.

[0102] In one exemplary implementation, with Co3O4 and H2 coexisting in the system, the enthalpy change (ΔH) of the solid-state reaction between BaCO3 and Al2O3 to form different products is theoretically checked using the reaction calculator module in the Materials Project. A mixed metallic precursor containing BaCO3, Al2O3, and Co3O4 is obtained after calcination in air prior to H2 heat treatment. Therefore, the reactants are set as BaCO3 + Al2O3 + Co3O4 + H2 (because the solid-state reaction occurs under an H2 atmosphere), and the possible products are set as all compounds containing Ba and any one or more of Co, Al, C, O, and H. A search of the Materials Project database yields 53 possible different products. The enthalpy change (ΔH) for each of the 53 possible products is then queried and sorted in the reaction calculator module, as follows: Figure 13 As shown. The stability of the corresponding product is evaluated by comparing the values ​​of ΔH. The lower the ΔH, the more stable the product. Figure 13 The three most stable products are Ba7Al. 64 O 103 BaAl4O7 and BaAl2O4. Given that BaAl4O7 (approximately 1100℃) and Ba7Al... 64 O 103 Given the reported high synthesis temperatures (above 1100℃, via solid-state reactions of BaAl4O7 and Al2O3), we focus on BaAl2O4 with Ba / Al = 1 / 2, which has milder synthesis conditions and is therefore more suitable for one-pot synthesis of the target Co@BaAl2O4 encapsulation structure combined with Taman temperature-guided synthesis.

[0103] In another exemplary embodiment, all possible products of the reaction MgCO3 + Al2O3 + CuO + H2 and their corresponding ΔH are ordered and plotted on a graph. Figure 34 In step a, this indicates that MgAl2O4 exhibits the lowest ΔH among all products considered in the MgCO3+Al2O3+CuO+H2 reaction. Therefore, MgAl2O4 is selected as the target capping layer for Cu NP. On the other hand, the formation of titanate capping layers can also be achieved when considering the solid-state reaction between BaCO3 and TiO2. A rapid calculation screening method is used ( Figure 35 a) Different titanate products with stoichiometric ratios were evaluated, among which BaTiO3 was one of the most frequently reported titanates. Therefore, BaTiO3 with Ba / Ti = 1 / 1 was selected as another target coating for Co NP.

[0104] exist Figure 1 Guided by the method described in section b, precursors of 40Ni:20Ba:40Al, 40Cu:20Mg:40Al, and 50Co:25Ba:25Ti were prepared. After heat treatment in H2, M T NP (Ni, Cu, or Co) and the corresponding M AE The formation of Al2O4 (BaAl2O4, MgAl2O4, or BaTiO3) can be confirmed by characteristic XRD patterns. Figure 33 (b, 34b, and 35b). STEM and energy-dispersive X-ray (EDX) spectra clearly visualize the encapsulation structures of Ni@BaAl2O4, Cu@MgAl2O4, and Co@BaTiO3, respectively, in which the well-encapsulated alkali metal aluminate or alkaline earth metal aluminate capping layer and M T NP close contact ( Figure 4 e). For Ni, Cu, and Co, the packaged M T The NPs exhibited relatively uniform size distributions of 4–8, 20–30, and 24–40 nm, consistent with the crystal sizes derived from XRD results. Figure 33 c, 34c, 35c and 54).

[0105] Depending on the selected first metal oxide, first encapsulation material, second encapsulation material, stoichiometry, and reaction conditions, the resulting core-shell nanoparticles can have an average size of 1-500 nm, 1-400 nm, 1-300 nm, 1-200 nm, 1-100 nm, 1-90 nm, 1-80 nm, 1-70 nm, 1-60 nm, 1-50 nm, 1-40 nm, 1-30 nm, 1-30 nm, 1-20 nm, 5-20 nm, 10-20 nm, 10-15 nm, 10-40 nm, 20-40 nm, 20-30 nm, or 1-10 nm. In some embodiments, the core-shell nanoparticles have an average size of about 10 to about 15 nm, about 4 to about 8 nm, about 20 to about 30 nm, and about 24 to about 40 nm.

[0106] The reaction of the first metal oxide, the first encapsulating material, and the second encapsulating material with hydrogen can be carried out under autogenous pressure (i.e., pressure generated by heating in a closed system). Alternatively or additionally, the pressure can be applied externally, for example, by mechanical means. In some embodiments, the step of heating the reaction solution is carried out at a pressure of 0.1 to 10 MPa or 0.1 to 1 MPa.

[0107] To fully utilize low T Tam M AE The high reactivity of CO3 suggests further functionalization of the BaCO3 capping layer during Co NP formation. This is based on the consideration of alkali metal aluminates or alkaline earth metal aluminates (i.e., M...). AE ) x Al y O z Al2O3 is a classic catalyst support material with high heat resistance, good hydrothermal stability, and significant interaction with active substances. This study attempts to introduce Al2O3 into encapsulation systems to design capping layer functionalization. Figure 2 a). A rapid calculation and ranking of the formation energies of different aluminate products from the solid-state reaction between BaCO3 and Al2O3 (a). Figure 2 b and Figure 13 The most suitable aluminate composition for the capping layer was determined to be BaAl2O4, rejecting the more stable BaAl4O7 and Ba7Al. 64 O 103 Because they require harsh synthesis conditions (>1100℃).

[0108] To achieve Co NP formation, BaCO3 encapsulation, and BaAl2O4 formation in a single heat treatment, the process begins with mixing Co, Ba, and Al metal precursors in a 40Co:20Ba:40Al composition via an automatically pH-controlled co-precipitation method, followed by temperature and flow-controlled air calcination. Figure 5After heat treatment in H2, the formation of Co NP and BaAl2O4 can be confirmed by characteristic X-ray diffraction (XRD) patterns. Figure 14 a). Scanning transmission electron microscopy (STEM) and energy-dispersive X-ray (EDX) spectra ( Figure 2 c) The encapsulation structure is clearly shown, in which the well-encapsulated BaAl2O4 capping layer is in close contact with the Co NP. The encapsulated Co NP exhibits a relatively uniform size distribution of 10-15 nm, consistent with the crystal size obtained from XRD. Figure 14 b and Figure 39 Transmission electron microscopy (TEM) images and corresponding FFT plots of Co@BaAl2O4 reveal the fcc Co and BaAl2O4 lattice fringes. Figure 15 This is related to the Co K-edge and Ba L3-edge extended X-ray absorption fine structure (EXAFS) ( Figure 2 d、 Figure 16-17 and Figures 40-43 ) and synchrotron X-ray diffraction (SXRD) results ( Figure 2 e) Completely identical.

[0109] Interestingly, the significant oxygen vacancies in the BaAl2O4 capping layer of Co@BaAl2O4 can be detected by X-ray photoelectron spectroscopy (XPS) and electron paramagnetic resonance (EPR) spectroscopy. Figure 18 a-18b). Furthermore, Ar adsorption-desorption analysis revealed the porous structure of Co@BaAl2O4 ( Figure 18 c-18d) is presumably due to the presence of oxygen vacancies during the synthesis of BaAl2O4 in an H2 environment. This porous feature is particularly important for catalysis because it endows reactant molecules with good core-shell permeability to approach the active metal core, while maintaining high stability due to encapsulation.

[0110] It is worth noting that the observed Co@BaAl2O4 encapsulation cannot be achieved by directly synthesizing BaAl2O4 (see [link]). Figure 19 and Figure 44 (details), which reflects the use of low T in our proposed SMSI packaging process. Tam The necessity of BaCO3.

[0111] Real-time observation and mechanism research of encapsulation

[0112] Further investigation was conducted into the synthesis process of Co@BaAl2O4 to explore the encapsulation formation pathway and mechanism. Starting from the 40Co:20Ba:40Al precursor, elemental composition analysis revealed that at different stages of the synthesis process (i.e., precipitation, calcination, and heat treatment in H2), Figure 20 and Figure 45Co, Ba, and Al have similar atomic ratios, approximately 2:1:2. However, TEM revealed different morphologies, in which encapsulation was formed only after heat treatment in H2. Figure 21 Then, the encapsulation process during H2 heat treatment was directly visualized in real time using an in-situ atmosphere STEM equipped with an environmental unit (experimental setup and details are available in [link to experimental setup]). Figure 8 At 25°C, the calcined precursor is initially a mixture of plate-shaped Co3O4 and rod-shaped Al2O3 NPs in contact with much larger blocky BaCO3. Figure 22 STEM images show a clear boundary between the dark Co3O4-Al2O3 mixture and the bright BaCO3 blocky particles. Figure 3 a). When the temperature rises above 400℃ ( Figure 3 (b) The boundaries of the BaCO3 particles become blurred, and some darker pores appear inside (marked by dashed circles). This can be attributed to the increased lattice mobility and subsequent outward diffusion, as evidenced by the boundary expansion (dashed lines). Increasing the temperature to 500℃ leads to more pronounced diffusion of BaCO3, forming darker pores inside, which is very consistent with the expanded Ba element distribution observed in the EDX elemental spectrum. Figure 23 a-23b). In contrast, no significant morphological changes were observed in the Co / Al-containing region until bright spheres appeared at 600°C and became more easily identifiable at 700°C. Figure 3 c) This indicates that CoNPs are formed in situ by the reduction of Co3O4. The Co NPs are surrounded by highly fluid or liquefied BaCO3, forming an initial encapsulation. When the cell is heated from 700°C to 800°C, a dynamic reaction can be observed at the expense of nearby Al2O3 rods, indicating the solid-state formation of a functional BaAl2O4 capping layer. Figure 3 d、 Figure 23 c) Such as selected area electron diffraction (SAED) Figure 23 As confirmed by d). Figure 3 The observed morphological evolution is summarized in section e, which is in complete agreement with our proposed SMSI-induced encapsulation strategy guided by Taman temperature.

[0113] To better understand the morphological evolution during H2 heat treatment, the initial morphology of the mixed metal precursor C(500)-40Co:20Ba:40Al before H2 heat treatment was characterized by TEM. Figure 22 As shown in Figure a, prior to H2 heat treatment, C(500)-40Co:20Ba:40Al was initially a mixture of plate-shaped Co3O4 and rod-shaped Al2O3 NPs in contact with much larger blocky BaCO3. A clear boundary was observed between the Co / Al-containing and Ba-containing regions. Figure 22The high-resolution TEM image and corresponding FFT shown in b reveal the polycrystalline nature of the BaCO3 structure, consistent with the above XRD results ( Figure 14 a) Consistent. Figure 22 The high-resolution TEM image shown in c indicates that Al2O3 exhibits a rod-like morphology, while Co3O4 exhibits a plate-like morphology, with its (220) lattice fringes in... Figure 22 Marked in d.

[0114] Figure 16 XANES characteristics of the samples at different stages of the synthesis process (i.e., precipitation, calcination, and heat treatment in H2) are shown. Before H2 heat treatment, C(500)-40Co:20Ba:40Al exhibits a much higher white line (WL) intensity compared to standard Co foil. After H2 heat treatment, the XANES distribution of C(500)-R(700)-40Co:20Ba:40Al shifts to lower energies and becomes similar to standard Co foil compared to C(500)-40Co:20Ba:40Al. These results indicate that metallic Co is formed by the reduction of Co3O4 during H2 heat treatment. Figure 16 b shows the Fourier transform (FT) amplitudes of the Co K-edge EXAFS of the samples at different stages of the synthesis process and the Co foil used for comparison. This is attributed to Co-Co... The peak amplitude of the Fourier transform (FT) is only present in C(500)-R(700)-40Co:20Ba:40Al, and not in 40Co:20Ba:40Al and C(500)-40Co:20Ba:40Al. These results prove that Co NPs can only be formed after H2 heat treatment. Figure 16 c and Figure 40 As shown, the EXAFS spectrum of C(500)-40Co:20Ba:40Al can fit the three paths well, corresponding to Co-O (coordination number, CN = 4.3) at the position. Co-Co (CN = 2.0) and The Co-Co / O structure at this location is in very good agreement with the theoretical Co3O4 model. Figure 41 Furthermore, the EXAFS spectrum of C(500)-R(700)-40Co:20Ba:40Al can be well fitted using only the Co-Co path, proving that the Co material after H2 heat treatment contains only metallic Co. Figure 16 d and 40).

[0115] The changes in the local structure of absorbed Co atoms can be observed more intuitively from the wavelet transform (WT) representation of the Co K-edge EXAFS signal. It can be clearly observed that C(500)-40Co:20Ba:40Al has a spectrum completely consistent with the theoretical Co3O4 model. Figure 12 e and 16g), while C(500)-R(700)-40Co:20Ba:40Al has a spectrum that is completely consistent with that of Co foil ( Figure 16 f and 16h) indicate that Co3O4 was reduced to Co metal during H2 heat treatment. This result is consistent with the XRD results above ( Figure 14 a) The observed structural changes are consistent.

[0116] Figure 17 a shows the Ba L3 edge XANES spectra of 40Co:20Ba:40Al, C(500)-40Co:20Ba:40Al, and C(500)-R(700)-40Co:20Ba:40Al. It can be observed that the edge positions remain unchanged between the three samples, indicating that the valence of Ba did not change significantly after air calcination and H2 heat treatment. Furthermore, the Ba L3 edge XANES spectrum of C(500)-R(700)-40Co:20Ba:40Al shows a unique peak from 5250 to 5285 eV. Figure 17 a) It conforms to the reported XANES characteristics of the BaAl2O4 structure. For example... As reported by [Authors' Name], a significant difference in the spectra between pure BaAl2O4 and pure BaCO3 is visible in the energy range of 5250 to 5270 eV. Specifically, BaCO3 exhibits absorption minimums at approximately 5255 eV and 5264 eV, while BaAl2O4 shows a stronger visible intensity within this energy range. From this comparison, it can be seen that the Ba L3 edge XANES spectra of the 40Co:20Ba:40Al and C(500)-40Co:20Ba:40Al samples follow the spectrum of the pure BaCO3 sample, while the C(500)-R(700)-40Co:20Ba:40Al follows the spectrum of BaAl2O4. This observation is consistent with XRD results from samples at different stages (…). Figure 14 a) Consistent with the observed phase transition.

[0117] From the Ba L3 edge EXAFS spectrum in R space, it can be observed that the spectra of 40Co:20Ba:40Al and C(500)-40Co:20Ba:40Al are similar, but significantly different from those of C(500)-R(700)-40Co:20Ba:40Al. Figure 14b). Ba L3 edge EXAFS fitting was also performed to identify the local structure of Ba. The EXAFS spectra of the 40Co:20Ba:40Al and C(500)-40Co:20Ba:40Al samples could be well fitted by the theoretical BaCO3 model, where ΔR ≤ 0.1 nm and R factor < 2%. Figure 14 c-14d, Figures 42-43 Furthermore, the EXAFS spectrum of C(500)-R(700)-40Co:20Ba:40Al can be well fitted using the theoretical BaAl2O4 model. Figure 17 e, Figures 42-43 ).

[0118] The structural changes can be observed more intuitively from the Ba L3 edge WT EXAFS. It can be clearly seen that the 40Co:20Ba:40Al and C(500)-40Co:20Ba:40Al samples have spectra completely consistent with the theoretical BaCO3 model. Figure 17 f, 17g, and 17i). In contrast, sample C(500)-R(700)-40Co:20Ba:40Al has a spectrum consistent with the theoretical BaAl2O4 model. Figure 17 h and 17j) indicate the phase evolution from BaCO3 to BaAl2O4 during H2 heat treatment. This result is consistent with the XRD results above ( Figure 17 a) The observed structural changes are consistent.

[0119] XRD and in-situ Raman spectroscopy with online MS (see...) Figure 7 Details in the XRD patterns were also used to supplement real-time phase evolution and solid-state reactions. In the initial stages, typical XRD patterns of BaCO3 and Co3O4 were recorded. Figure 3 f), in which there is no Al2O3 fingerprint peak, presumably submerged by the Co3O4 signal or the nanocrystalline nature of the γ-phase Al2O3 ( Figure 22 d). As the heat treatment temperature increased to 400 °C, the characteristic peaks of Co3O4 at 31.27 °C and 36.84 °C gradually disappeared, while two new peaks appeared at 44.22 °C and 51.52 °C, which can be designated as fcc Co. At 700 °C, the characteristic diffraction signal of BaCO3 was replaced by the characteristic diffraction signal of BaAl2O4, indicating that the solid-state reaction between BaCO3 and Al2O3 had been completed. Similarly, in-situ Raman spectroscopy revealed that before 400 °C, characteristic peaks were observed at approximately 490, approximately 525, approximately 610, and approximately 690 cm⁻¹. -1 The nearby Co3O4 fingerprint gradually disappeared, and at 700°C, at approximately 139, 698, and 1060 cm⁻¹, the fingerprints were also observed. -1 Nearby BaCO3 fingerprints were found at approximately 193, 271, 491, 581, and 680 cm.-1 Nearby BaAl2O4 fingerprint replacement ( Figure 3 g). Online MS was used to monitor the outlet gas during the H2 downflow heat treatment process. It was observed that Co3O4 was reduced during the 300–500 °C period, while H2 was consumed and H2O was released. As the temperature further increased to 700 °C, the CO and H2O peaks rose rapidly while H2 was consumed, consistent with the solid-state reaction between BaCO3 and Al2O3. In other words, these results correspond to the phase transition processes observed in in-situ STEM. Note that the differences in some phase transition temperatures recorded by different characterization techniques are due to different in-situ conditions and do not affect the trend of the identified phase evolution and encapsulation mechanisms.

[0120] All the evidence together indicates that (i) low T Tam BaCO3 exhibits sufficient mobility to migrate to in-situ formed Co NPs, and (ii) BaCO3 can readily react with Al2O3 to form BaAl2O4 as the final encapsulation capping layer (i.e., BaCO3 + Al2O3 + H2 → BaAl2O4 + CO + H2O), thanks to the low T Tam BaCO3 exhibits high reactivity in a H2 atmosphere at relatively high temperatures. Therefore, complete encapsulation of BaAl2O4 on a Co NP surface was achieved by forming a well-defined core@shell structure.

[0121] Encapsulated nanocatalysts can achieve excellent catalytic performance.

[0122] To evaluate the effect of BaAl2O4 encapsulation on the catalytic performance of Co NP at high temperatures, the performance of a series of encapsulated and unencapsulated Co nanocatalysts in the thermocatalytic decomposition of NH3 was assessed. Typically, this reaction requires non-noble metal catalysts at temperatures of approximately 650–800 °C to achieve NH3 conversions exceeding 80% without sacrificing the weight hourly space velocity (WHSV). Surprisingly, Co@BaAl2O4 showed improved performance at a much lower temperature of only 500 °C at a concentration of 30,000 mL g / L. cat -1 h -1 Achieving near-complete conversion (approximately 99%) at high WHSV levels. Figure 26 and Figure 46 This makes it the best core-shell catalyst reported to date for NH3 decomposition. Figure 4 a). Compared with existing NH3 decomposition catalysts, encapsulated Co@BaAl2O4 is also one of the most effective catalysts recorded for Ru-based and non-noble metal catalysts. Figure 27 and Figure 47 ).

[0123] The most significant advantage of the core@shell catalyst structure is demonstrated in long-term performance evaluation. After 50 hours of continuous operation at 550°C, the unencapsulated catalyst (Co NP supported on Al2O3 (Co / Al2O3) and BaAl2O4) showed superior performance (see synthesis details for details). Figure 19 The H2 production of the Co particles decreased significantly, indicating that the long-term activity was poor due to severe sintering of the Co particles under high-temperature reaction conditions. Figure 4 b, 4c, Figures 28-29 and Figures 48-49 In stark contrast, under the same testing conditions, the Co@BaAl2O4 nanocatalyst maintained a constant high H2 productivity even after 600 hours. Figure 4 b). No significant changes in morphology were observed in Co@BaAl2O4 after the reaction. Figure 4 d、 Figure 30 and Figure 50 This indicates that it possesses excellent thermochemical stability due to its favorable core@shell structure. EXAFS of Co@BaAl2O4 after the reaction shows distinct Co and BaAl2O4 phases. Figure 30 , Figure 51 and Figure 52 This indicates that no Co migration occurred at the metal-support interface during the long-term testing period. Notably, despite intentional temperature fluctuations, system ON / OFF cycles, and catalyst unloading / reloading events, the activity of Co@BaAl2O4 did not decrease during the five-month experiment. Figure 31 This indicates that it has excellent environmental tolerance and reusability in practical applications.

[0124] Furthermore, Co@BaAl2O4 has shown promising results in CH4 dry reforming reactions that typically require even higher temperatures (>750 °C). For example... Figure 32 As shown, Co@BaAl2O4 achieved CH4 and CO2 conversions of 81.8% and 90.1%, respectively, close to the thermodynamic equilibrium values ​​and maintained this performance for over 60 hours. Compared with the benchmark catalysts reported in the literature ( Figure 53 The high efficiency and excellent stability of Co@BaAl2O4 indicate its promising potential as a catalyst for the CH4 dry reforming reaction. These results collectively demonstrate that our novel encapsulation strategy not only effectively stabilizes the nanocatalyst for common sintering problems but also provides opportunities for further performance modifications to achieve good catalytic applicability. Currently, the reasons for the superior performance of Co@BaAl2O4 in the aforementioned thermocatalytic reactions are still under close investigation, focusing on the significant synergistic effect of the metal-support interface in the core@shell structure.

[0125] A widely applicable core@shell catalyst design and synthesis platform

[0126] Low T has been successfully proven Tam The compounds can facilitate the thermally induced construction of SMSI core@shell structures, and subsequent solid-state reactions for capping functionalization enable thermocatalytic applicability. Furthermore, to demonstrate the general applicability of our proposed method, encapsulation windows ( Figure 1 Other M in the shaded area (b) T and M AE The CO3 combination was tested. The results validated the effectiveness of our Taman temperature-guided heat sealing and sintering prevention strategy. Figure 4 e Figures 33-34 and Figure 54 Even more convincingly, using TiO2 instead of Al2O3 for the solid-state reaction of the capping layer allows us to achieve BaTiO3 encapsulation of Co NPs. Figure 4 e Figure 35 and Figure 54 This demonstrates the broad applicability of our strategy in various material matrices.

[0127] All these results demonstrate that the Taman temperature-guided SMSI strategy is a viable option for M T The potential of NP-compatible packaging design and synthesis platforms. T The tunability of the core and functional oxide capping layer shows promise for fine-tuning the performance of encapsulated nanocatalysts. Other low-T... Tam Metal compounds, such as chlorides, sulfates, and nitrates, can also be used to construct size-controlled encapsulation structures for different transition metal nanoparticles (NPs) (in-situ reduction or pre-fabricated metal NPs). Computational calculations can facilitate rapid compositional selection from a wide range of material matrices used for solid-state reactions of the capping layer, unlocking extensive possibilities for metal oxides (or non-oxides) to act as NP protectors / modifiers. Overall, this novel thermal encapsulation method enables future exploration and prediction of the rational and dynamic tuning of nanocatalysts to meet diverse requirements in a wide range of energy and environmental applications.

[0128] Example

[0129] Materials and Instruments

[0130] Ferric nitrate nonahydrate (Fe(NO3)3·9H2O, 99.0%), cobalt nitrate hexahydrate (Co(NO3)2·6H2O, 99.0%), nickel nitrate hexahydrate (Ni(NO3)2·6H2O, 99.0%), copper nitrate (Cu(NO3)2, 99.0%), magnesium carbonate (MgCO3, AR), calcium carbonate (CaCO3, AR), strontium carbonate (SrCO3, AR), anhydrous barium carbonate (BaCO3, AR), sodium carbonate (Na2CO3, 99.0%), and sodium hydroxide (NaOH, 96.0%) were purchased from Shanghai Aladdin Bio-Chem Technology Co., Ltd. Barium nitrate (Ba(NO3)2, 99.0%) and aluminum nitrate nonahydrate (Al(NO3)3·9H2O, 99.0%) were purchased from Sigma-Aldrich. Nano-iron oxide (Fe2O3, 99.0%), nano-cobalt oxide (Co3O4, 99.0%), nano-nickel oxide (NiO, 99%), and nano-copper oxide (CuO, 99%) were purchased from Shanghai Macklin Biochemical Co., Ltd. Unless otherwise specified, all analytical grade chemicals were used directly without further processing. All solutions were prepared using deionized (DI) water. Anhydrous ammonia (NH3, ≥99.99%) and H2 / Ar (v / v, 5 / 95) were purchased from Scientific Gas Engineering Co., Ltd.

[0131] Precursor coprecipitation synthesis method and heat treatment

[0132] The precursor mixture mMT:nMAE:2nAl was synthesized via an automated pH-controlled co-precipitation method. For a typical preparation process, M containing the target molar ratio was prepared by dissolving the corresponding metal nitrate in an aqueous solution. T m+ M AE 2+ And Al 3+ An aqueous solution of Na₂CO₃ was added dropwise to a stirred tank reactor (500 mL - 2 L capacity) containing 0.5 M Na₂CO₃ solution at room temperature at a feed rate of 0.1 - 2.0 mL / min. -1 The pH of the precipitate solution was adjusted using a syringe pump. The mixture was vigorously stirred to ensure effective mixing, while the pH was carefully maintained constant by adding 4.0M NaOH solution dropwise using another syringe pump. The pH of the solution was kept below M. AE The precipitation of (OH)2 pKsp facilitates the formation of MAE CO3 instead of M AE (OH)₂ precipitate. The pKsp of Ba(OH)₂ is 12.9, and that of Mg(OH)₂ is 10.10. Once the pre-measured amount of solution was added to the vessel, the liquid was aged for 16 hours, then the mixture was filtered and washed with deionized water until the pH was close to 7.0. The resulting wet cake solid sample was redispersed in 200 mL of acetone and stirred at room temperature for 2 hours. The resulting solid was then vacuum filtered, thoroughly washed with acetone, and dried overnight in a vacuum oven at room temperature. The precursors were named according to their nominal mixed metal ratios and expressed as mM. T :nM AE :2nAl, where m and n represent M respectively T and M AE The nominal molar ratio in the coprecipitation process. (The remaining text appears to be incomplete and requires further context.) T :nM AE After precipitating 2nAl, it is calcined in air (expressed as C (temperature) - mM). T :nM AE :2nAl) and at the specified temperature in H2 / Ar (v / v, 5 / 95, 160mL min per 50mg sample) -1 The temperature is processed in the process to ultimately form a possible package structure, represented as C(temperature)-R(temperature)-mM. T :nM AE :2nAl(To visually indicate the sample structure through the sample name, if the final sample has a core-shell structure, it is also represented as M. T @M AE Al2O4. C (temperature) and R (temperature) indicate the air calcination and H2 treatment processes, and the highest temperature (°C) reached in each process is listed in parentheses. Figure 5 A schematic diagram illustrating the steps involved in the above synthesis process is provided.

[0133] M AE CO3 decomposition temperature (T) dec Measurement of )

[0134] Commercially available alkali metal carbonates or alkaline earth metal carbonates (M) were analyzed using a tube furnace (GSL-1100X, Kejing) combined with a quadrupole mass spectrometer (MS, HPR-20EGA, Hiden). AE CO3, M AE The temperature-programmed decomposition measurement of (Na, K, Rb, Cs, Mg, Ca, Sr, Ba, etc.) was performed. Approximately 50 mg of M was placed in a quartz tube. AE The CO3 sample was sandwiched between two layers of quartz wool, allowing the thermocouple to contact the sample. The quartz tube was then inserted into a tube furnace for argon (Ar) pretreatment at a flow rate of 10 mL / min.-1 At 5℃ min -1 The heating rate increased the temperature from 25°C to 50°C, and then held at 50°C for 30 minutes. Ar pretreatment cleaned the catalyst surface by removing adsorbed ambient gas molecules. After pretreatment, in order to decompose M... AE CO3, H2 / Ar (5 / 95, v / v) gas at 10 mL / min -1 The flow rate passes through the quartz tube at 5°C / min. -1 The heating rate increased the temperature from 25°C to 800°C (950°C for BaCO3). The outlet gas products, including H2O (m / z = 18), CO (m / z = 28), and CO2 (m / z = 44), were recorded by MS as a function of temperature.

[0135] M T O x reduction temperature (T) red Measurement of )

[0136] Nanoscale commercially available metal oxides were analyzed using a tube furnace (GSL-1100X, Kejing) combined with four-electrode mass spectrometry (HPR-20EGA, Hiden). T O x M T The temperature-programmed reduction measurement of (Fe, Co, Ni, Cu) was performed. Approximately 50 mg of M was placed in a quartz tube. T O x The sample was sandwiched between two layers of quartz wool, ensuring contact between the thermocouple and the sample. The quartz tube was then inserted into a tube furnace for Ar pretreatment at a flow rate of 10 mL / min. -1 At 5℃ min -1 The heating rate increased the temperature from 25°C to 50°C, and then held at 50°C for 30 minutes. Ar pretreatment cleaned the catalyst surface by removing adsorbed ambient gas molecules. After pretreatment, in order to reduce M... T O x H2 / Ar (5 / 95, v / v) gas at 10 mL / min -1 The flow rate passes through the quartz tube at 5°C / min. -1 The heating rate increased the temperature from 25°C to 800°C (950°C for Fe₂O₃). M T O x Reduced to M T NP produces H2O during heat treatment. The variation of the gaseous product H2O (m / z = 18) with temperature was recorded by MS.

[0137] Theoretical estimation of solid-state reaction energy

[0138] Use the reaction calculator module in the Materials Project to estimate the amount of M AE CO3 and Al2O3 form different alkali metal aluminates or alkaline earth metal aluminates (M AE The reaction energy of Al2O4. Details can be found in Figure 13 .

[0139] Material characterization

[0140] X-ray diffraction (XRD) was performed using a parallel-beam XRD instrument (Rigaku SmartLab 9kW-Advance, using wavelength...). The phase and crystal structure of the Cu(Kα) samples were characterized by powder X-ray diffraction (XRD). For measurements of the reduced and post-reaction samples, the samples were protected in a reaction tube sealed at both ends with closed ball valves and directly transferred to an inert gas glove box. In the inert gas glove box, the samples were removed from the reaction tube and placed in a quartz holder, then covered with a Kapton membrane. Figure 6 In this airtight XRD holder, the gas-sensitive sample is kept isolated from the air and can be directly measured by an XRD device.

[0141] Using the Debye-Scherrer equation The crystallite size (D) is estimated by XRD, where k is the shape factor of the reciprocal lattice and the crystal shape factor in direct space (k = 0.9), λ is the wavelength of the incident radiation, β is the full width at half maximum (FWHM), and θ is the Bragg angle.

[0142] Synchrotron X-ray diffraction (SXRD) uses the powder diffraction (PD) beamline of the Australian Synchrotron (AS) to collect SXRD patterns, setting them up to provide... The photon energy was determined. Each capillary was mounted on the head of a crystal goniometer and rotated at 15 rpm. The pattern was measured using Debye-Scherrer geometry, with a goniometer diameter of 152 cm, a 2θ range of 1.01398° to 80.8344°, and an effective step size of 0.00375°. The SXRD incident and diffracted beams were fully polarized.

[0143] Each sample was measured twice, with the Mythen detector offset by 0.5° during the second data acquisition. The two offset patterns were merged using the PDViPeR program. Another pattern of the NIST SRM-660b LaB6 powder was measured under the same conditions to determine the instrument wavelength, 2θ0 correction, and instrument FWHM width of the Bragg peak.

[0144] Diffraction patterns were analyzed using a TOPAS(V6)-based Rietveld refinement method to obtain structural details. The Thompson-Cox-Hastings pseudo-Voigt peak function was applied to describe the diffraction peaks. Scaling factors and lattice parameters were allowed to refine all diffraction patterns. The quality of the Rietveld refinement of synchrotron data was ensured by well-fitted patterns with low Goodness-of-Fit (GoF) factors, low weighted profile factors (Rwp), and acceptable temperature factors (Beq) within experimental error.

[0145] Transmission electron microscopy (TEM) was used to characterize the microstructure and phase information of the samples using scanning transmission electron microscopy (STEM) in high-angle annular dark field (HAADF) mode and dual-Cs calibrated STEM (Spectra300, TFS, USA) equipped with a Super-X energy-dispersive X-ray spectrometer (EDX) and a STEM / TEM (JEM-2100F, JEOL, Japan) combined with a Gatan Enfina electron spectrometer (USA). TEM samples were prepared by sonicating an appropriate amount of material in 1 mL of ethanol for 180 seconds, followed by dropping the solution onto a copper grid. For both reduced and post-reaction samples, the samples were protected in reaction tubes sealed at both ends with closed ball valves and directly transferred to an inert gas glove box, where the samples could be removed from the reaction tubes and dispersed in an ethanol solution for further deposition onto the copper grid.

[0146] Scanning electron microscopy (SEM) images were recorded on a Tescan VEGA3 GMH microscope using energy-dispersive X-ray diffraction (SEM-EDX) with an accelerating voltage of 5 kV. The atomic ratios of metallic elements (including Co, Ba, and Al) in the samples were measured using EDX.

[0147] Electron paramagnetic resonance (EPR) analysis was performed using a Bruker EMX Plus spectrometer equipped with a dual-mode cavity (ER 4116DM). The microwave frequency and power were 9.83 GHz and 3.17 mW, respectively. The sample weight was 50.0 mg.

[0148] X-ray absorption fine structure (XAFS) measurements were performed in fluorescence mode using a Lytel detector at the BL01C beamline of NSRRC. Photon energies were scanned using a Si(111) dual-crystal monochromator (DCM). To ensure the reproducibility of the experimental data, at least two scans were collected for each sample and compared. Background subtraction and normalization of the X-ray absorption near-edge structure (XANES) data were performed using the AUTOBK routine in Athena software. Quantitative information on the radial distribution of neighboring atoms around Co and Ba atoms was derived from the extended absorption fine structure (EXAFS) data. The EXAFS x-function was extracted from the raw experimental data using the IFEFFIT software, employing an established data reduction method. For wavelet transform, k... 3 Weighted EXAFS spectrum. Morlet wavelet mother functions are applied to the Co-K edges respectively. and Ba L3 side The wavelet transform (WT) of all spectra within the k-range is used. The selection of this wavelet is controlled by the fast oscillating part located in the Gaussian envelope, making the real and imaginary parts similar to the EXAFS spectrum.

[0149] X-ray photoelectron spectroscopy (XPS) experiments were performed using a Thermo Scientific Nexsa instrument equipped with an electron beam and scanning ion gun. The binding energy (BE) was calibrated using the C1 s-line (284.8 eV) of the amorphous carbonaceous material. Following Shirley background differentiation, the XPS spectra were deconvolved using a Gaussian-Lorentz function, and the integrated peak area was used to estimate the surface chemical composition.

[0150] In a typical in-situ Raman measurement process, approximately 5 mg of sample was loaded into an in-situ Raman unit, allowing H2 / Ar (5 / 95, v / v) to pass through the sample. A series of Raman spectra were obtained at different temperatures ranging from room temperature to 700 °C at intervals of 50 °C to investigate the phase transition during H2 heat treatment. Each temperature was set for a dwell time of 40 minutes, and spectra were collected when steady state was reached at the 30-minute mark. In-situ Raman spectra were recorded using a WITEC confocal microscope system equipped with a 532 nm laser diode. The laser was focused onto the sample using a 50× objective lens, with a laser spot size of 1 μm. Raman measurements were performed by irradiating with a 3 mW laser power, with a cumulative time of 60 s and 10 cumulative measurements. Figure 11 The in-situ Raman setup is shown. Equipped with a quadrupole MS (HPR-20EGA, Hiden), the composition and concentration of the outlet gas were analyzed, and the changes of H2 (m / z = 2), H2O (m / z = 18), and CO (m / z = 28) with temperature were recorded.

[0151] In-situ STEM was used to achieve direct visualization of the Co@BaAl2O4 encapsulation process via in-situ atmosphere STEM research (JEOL JEM-2100F). During in-situ STEM observation, a Protochips Atmosphere gas holder was applied. Figure 8 a) In this experiment, a flowing gas can be injected and the temperature can be controlled. In this experiment, 380 Torr H2 / N2 (5 / 5, v / v) was used at a flow rate of 0.1 mL / min, and the temperature was set between 25 and 800 °C.

[0152] The effect of the electron beam was carefully evaluated by comparing the sample states inside and outside the observation area. First, the initial precursor C(500)-40Co:20Ba:40Al was prepared on the bottom unit and characterized by STEM and EDX before heating the in-situ unit. The bottom unit was then assembled in an in-situ holder, into which a H2 / N2 mixture was injected. The temperature was gradually increased to 300, 400, 500, 600, 700, and 800 °C at a rate of 20 °C / min. Each target temperature was held for 30 minutes to allow for a complete reaction. Figure 8 An in-situ STEM device is shown. This is achieved by injecting gas and sealing it within two windowed silicon wafers (…). Figure 8 The space between the electronic chip products from Protochips (shown in b) makes it possible to introduce gas into the vacuum environment of the TEM. The windowed silicon wafer has a notch near its center and is covered with an 80nm thick amorphous silicon nitride film as a window.

[0153] NH3 decomposition performance test method and apparatus

[0154] Figure 9 This is a schematic diagram of the NH3 decomposition performance testing apparatus. To measure the catalytic performance of the designed catalyst in the 4.5 mm diameter quartz tube for NH3 decomposition, approximately 50 mg of sieved (45-80 mesh) sample was sandwiched between two layers of quartz wool, with a thermocouple in contact with the sample. High-purity NH3 (≥99.99%) was then passed through the catalyst bed, with the flow rate controlled by a mass flow controller. At atmospheric pressure, the weight hourly space velocity (WHSV) was set to 30,000 mL g / cm³. cat -1 h -1 The concentrations of N2, H2, and NH3 at the outlet after the reaction were measured online using an MS (HPR-20EGA, Hiden) equipped with a quadrupole probe and a secondary electron multiplier detector (850 eV). The accuracy of the product analysis was further verified by back titration. Figure 25 b). The measured temperature range was 450 to 650°C, with intervals of 50°C, and steady state was achieved by holding each temperature for 60 minutes.

[0155] The NH3 conversion rate is calculated using the following Equation 1.

[0156]

[0157] Among them, [NH3] 入口 and [NH3] 出口 This refers to the measured concentration of NH3 entering and exiting the reactor.

[0158] The unit is mmol H2 g cat -1 min -1 H2 productivity is obtained from NH3 conversion rate (X) via the following equation 2. NH3 )calculate:

[0159]

[0160] WHSV is the weight hourly space velocity (30,000 mL g). cat -1 h -1 ), X NH3 It is the conversion rate of NH3, V m This is the molar volume of the gas at 25℃ and 1 atm (24 mL mmol). -1 ).

[0161] To verify the reliability of the performance testing equipment, two benchmark catalysts were synthesized according to the reported methods: Ru / MgO synthesized via the polyol method and Ru / Al2O3 synthesized via the coprecipitation method. Our equipment was used to test the catalysts at 500–650 °C and 30,000 mL g / L. cat -1 h -1 Its NH3 decomposition performance was tested under WHSV. The results were compared with reported values. Figure 25 As shown in Figure a, the NH3 conversion rate we measured is almost identical to that reported in the literature, indicating that our performance testing equipment is reliable. Furthermore, to ensure the accuracy of the reaction product analysis method, MS analysis and back titration experiments were used to analyze the NH3 content in the outlet gas. Figure 25 b). The experimental details of the back titration analysis have been reported in our previous study. It can be observed that the results of the two analytical methods are consistent, with only a small difference of less than 3% in the NH3 conversion rate, thus confirming the accuracy of our reaction product composition analysis method.

[0162] Methane dry reforming performance test

[0163] The catalytic dry reforming activity of methane (CH4) was tested in a fixed-bed quartz reactor (5 mm inner diameter) at atmospheric pressure. Before each reaction, 100 mg of catalyst was placed in the reaction tube between quartz cotton plugs, and the reaction was carried out at 700 °C in a flowing H2 / Ar (5 / 95, v / v, 60 mL / min) atmosphere. -1 In-situ reduction for 2.5 hours. Then, at 750°C, a mixture of CO2 / CH4 in Ar (45 / 45 / 10, v / v / v, 53 mL / min) was used. -1 (Total flow rate) to produce 31,765 mL g cat -1 h -1 The heavy space velocity (WHSV) was used to dry reform CH4. Reactant and product concentrations were analyzed online using an MS (QGA, Hiden) equipped with a quadrupole probe and a secondary electron multiplier detector. CH4 and CO2 conversions were calculated according to Equations 3 and 4 below, respectively:

[0164]

[0165]

[0166] Where [CH4] and [CO2] are the corresponding mole fractions of CH4 and CO2 in the stream, and F 入口 and F 出口 These represent the total gas flow rates (mL / min) at the inlet and outlet, respectively. -1 ).

[0167] The selectivity of H2 and CO is expressed by the following equations 5 and 6:

[0168]

[0169]

Claims

1. A method for preparing core-shell nanoparticles, the method comprising: A mixture comprising a first encapsulation material containing a first metal oxide, an alkali metal or alkaline earth metal salt, and a second encapsulation material containing a second metal oxide is brought into contact with hydrogen at a temperature higher than the hydrogen reduction temperature of the first metal oxide and lower than the decomposition temperature of the first encapsulation material. This causes the first metal oxide to be reduced and form metal nanoparticles at least partially encapsulated by a bimetallic oxide containing the alkali metal or the alkaline earth metal and the second metal, thereby forming the core-shell nanoparticles, wherein the Taman temperature of the first encapsulation material is lower than the hydrogen reduction temperature of the first metal oxide.

2. The method according to claim 1, further comprising providing screening data on the enthalpy changes of the reaction products of the reaction of the candidate first metal oxide, the candidate first encapsulation material, the candidate second encapsulation material and hydrogen; and selecting the first encapsulation material and the second encapsulation material based on the screening data and the decomposition temperature of the candidate first encapsulation material.

3. The method of claim 2, wherein the filtering data is generated using a computer.

4. The method according to claim 1, further comprising selecting the first encapsulation material and the second encapsulation material based on the hydrogen reduction temperature of the first metal oxide, the decomposition temperature of the first encapsulation material, and the Taman temperature of the first encapsulation material.

5. The method according to claim 1, wherein the metal of the first metal oxide comprises a metal selected from the group consisting of V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Mo, Se, Sn, Pt, Ru, Pd, W, Ir, Os, Rh, Nb, Ta, Pb, Bi, Au, Ag, Sc and Y.

6. The method according to claim 1, wherein the first metal oxide is selected from the group consisting of CoO3, Co3O4, CoO, CuO, Cu2O, NiO, Ni2O3, Ag2O, AgO, FeO, Fe2O3, Fe3O4, ZnO, PdO, PdO2, PtO and PtO2.

7. The method according to claim 1, wherein the anion of the alkali metal or alkaline earth metal salt comprises one or more anions selected from the group consisting of carbonate, sulfate, nitrate, chloride, phosphate and acetylacetone anions.

8. The method according to claim 1, wherein the first encapsulation material comprises CaCO3, MgCO3, SrCO3, BaCO3, NaCl, KCl, RbCl, Na2CO3, K2CO3 or Rb2CO3.

9. The method according to claim 1, wherein the second metal oxide comprises Al2O3, TiO2, SiO2, Ga2O3, In2O3, ZrO2, or a mixture thereof.

10. The method according to claim 8, wherein the first metal oxide is selected from the group consisting of CoO3, Co3O4, CuO, Cu2O, NiO, Ni2O3, Ag2O, AgO, FeO, Fe2O3, Fe3O4, ZnO, PdO, PdO2, PtO, and PtO2.

11. The method according to claim 1, wherein the bimetallic oxide comprises MgAl2O4, CaAl2O4, SrAl2O4, BaAl2O4, MgTiO3, CaTiO3, SrTiO3, BaTiO3, MgGa2O4, CaGa2O4, SrGa2O4, BaGa2O4, MgIn2O4, CaIn2O4, SrIn2O4, BaIn2O4, MgZrO3, CaZrO3, SrZrO3, or BaZrO3.

12. The method of claim 1, wherein each of the core-shell nanoparticles comprises a shell and a core, the shell comprising MgAl2O4, CaAl2O4, SrAl2O4, BaAl2O4, MgTiO3, CaTiO3, SrTiO3, BaTiO3, MgGa2O4, CaGa2O4, SrGa2O4, BaGa2O4, MgIn2O4, CaIn2O4, SrIn2O4, BaIn2O4, MgZrO3, CaZrO3, SrZrO3, or BaZrO3, and the core comprising Co, Cu, Ni, Ag, Fe, Zn, Pd, or Pt.

13. The method according to claim 1, wherein the core-shell nanoparticles are selected from the group consisting of Co@BaAl2O4, Cu@BaAl2O4, Ni@BaAl2O4, Co@BaTiO3, Fe@MgGa2O4, Co@MgGa2O4 and Ni@BaZrO3.

14. The method of claim 13, wherein the core-shell nanoparticles have an average diameter of 10 nm to 15 nm.

15. The method of claim 1, further comprising calcining the mixture prior to the step of contacting the mixture with hydrogen.

16. The method of claim 15, wherein calcination is performed below the decomposition temperature of the first encapsulation material.

17. The method according to claim 1, further comprising contacting a first metal nitrate, an alkali metal or alkaline earth metal nitrate, a second metal nitrate, and an alkali metal carbonate to form a coprecipitate; and calcining the coprecipitate to form the mixture.

18. The method of claim 7, further comprising providing screening data on the enthalpy change of the reaction products of the reaction of the candidate first metal oxide, the candidate first encapsulation material, the candidate second encapsulation material and hydrogen; And the first encapsulation material and the second encapsulation material are selected based on the screening data and the decomposition temperature of the candidate first encapsulation material; The first encapsulation material and the second encapsulation material are selected based on the hydrogen reduction temperature of the first metal oxide, the decomposition temperature of the first encapsulation material, and the Taman temperature of the first encapsulation material.

19. The method of claim 18, wherein the metal of the first metal oxide comprises a metal selected from the group consisting of V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Mo, Se, Sn, Pt, Ru, Pd, W, Ir, Os, Rh, Nb, Ta, Pb, Bi, Au, Ag, Sc and Y.

20. The method of claim 19, further comprising contacting a first metal nitrate, an alkali metal or alkaline earth metal nitrate, a second metal nitrate, and an alkali metal carbonate to form a coprecipitate; and calcining the coprecipitate to form the mixture.

Citation Information

Patent Citations

  • Alkaline-earth metal oxide supported ruthenium catalyst, and preparation method and application thereof

    CN112973679A